1998
DOI: 10.1046/j.1365-2842.1998.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of four composite veneering materials polymerized with different laboratory photo‐curing units

Abstract: This study examined properties of four composite veneering materials polymerized with two different photo-curing units for the purpose of evaluating curing performance of the combination of composite material and curing unit. Two microfilled (Dentacolor and Thermoresin LC II) and two hybrid (Cesead II and Solidex) composite materials designed for prosthetic veneer were selected. The respective light sources of the units were a xenon (Dentacolor XS) and a metal halide (Hyper L II) lamp. The composite materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 16 publications
1
46
0
1
Order By: Relevance
“…The composition of these indirect, veneering composite resin systems is similar to that of the direct composite resins, but they differ in additional polymerization. 12 The mechanical and physical properties of veneering composite resins are based on their chemical composition: resin matrix, 13,14 filler particle type, 14 filler size, 15 filler percentage, 15,16 and filler-matrix bonding (silane coupling agent). 16,17 Temperature, 17,18 environmental conditions, 19 and light intensity of 18931-rev2-figs edits 3 the polymerization unit are all important factors.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of these indirect, veneering composite resin systems is similar to that of the direct composite resins, but they differ in additional polymerization. 12 The mechanical and physical properties of veneering composite resins are based on their chemical composition: resin matrix, 13,14 filler particle type, 14 filler size, 15 filler percentage, 15,16 and filler-matrix bonding (silane coupling agent). 16,17 Temperature, 17,18 environmental conditions, 19 and light intensity of 18931-rev2-figs edits 3 the polymerization unit are all important factors.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of high-intensity light-polymerizing units on the hardness of light-activated composites has been reported by many researchers (6,9,15). The KHN test results with the greatest values were generated with the TH and LI units, possibly signifying that these two units have higher light intensities than AL.…”
Section: Discussionmentioning
confidence: 65%
“…All the KHN testing results were considerably low when compared with those for the other indirect composites (9). It might be because of the lower filler content of the material (44.7 wt%).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Studies have shown that one such metal halide unit improved depth of cure (10) and hardness (2,11,12) of materials. In addition, use of a metal halide unit considerably reduced water solubility (1,11) and wear of indirect composites (3).…”
Section: Introductionmentioning
confidence: 99%